2018
DOI: 10.1002/cnma.201800194
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Amphiphiles for Addressable Supramolecular Nanostructures

Abstract: In this focus review we aim to highlight an exciting class of materials, electroactive amphiphiles (EAAs). This class of functional amphiphilic molecules has been the subject of sporadic investigations over the last few decades, but little attempt has been made to date to gather or organise these investigations into a logical fashion. Here we attempted to gather the most important contributions, provide a framework in which to discuss them, and, more importantly, point towards the areas where we believe these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 103 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…Despite these current limitations, the approaches taken in these associated fields that employ self-assembly techniques demonstrate the tuneability and feasibility of developing 3D conductive self-assembling networks for neural repair. 342 , 343 For example, highly conductive BTBT amphiphiles are commonly formed in organic solvents, but recently, it has been demonstrated that self-assembly of these molecules can be achieved in aqueous conditions, in a first step toward a tissue engineering application. 344 Interest in these π-conjugated peptides for biomaterial applications will continue to grow because of the tuneability and nontoxic nature of self-assembling electroactive molecules.…”
Section: Considerations For Electrical Stimulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these current limitations, the approaches taken in these associated fields that employ self-assembly techniques demonstrate the tuneability and feasibility of developing 3D conductive self-assembling networks for neural repair. 342 , 343 For example, highly conductive BTBT amphiphiles are commonly formed in organic solvents, but recently, it has been demonstrated that self-assembly of these molecules can be achieved in aqueous conditions, in a first step toward a tissue engineering application. 344 Interest in these π-conjugated peptides for biomaterial applications will continue to grow because of the tuneability and nontoxic nature of self-assembling electroactive molecules.…”
Section: Considerations For Electrical Stimulationmentioning
confidence: 99%
“…Furthermore, the stability and degradation of electroactive scaffolds in physiological environments is not well understood. Despite these current limitations, the approaches taken in these associated fields that employ self-assembly techniques demonstrate the tuneability and feasibility of developing 3D conductive self-assembling networks for neural repair. , For example, highly conductive BTBT amphiphiles are commonly formed in organic solvents, but recently, it has been demonstrated that self-assembly of these molecules can be achieved in aqueous conditions, in a first step toward a tissue engineering application . Interest in these π-conjugated peptides for biomaterial applications will continue to grow because of the tuneability and nontoxic nature of self-assembling electroactive molecules. , Understanding the various methods that have been used to tailor the electronic properties of π-conjugated oligomer self-assembling systems is crucial to determining their compatibility for neural tissue engineering.…”
Section: Considerations For Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-assembly is the simplest approach toward the production of highly ordered functional assemblies of molecules in a wide range of interesting morphologies (e.g., various micellar structures, nanorods, nanoribbons, nanofibers, amongst others) (Gröschel and Müller, 2015; Townsend et al, 2018). Such structures have potential applications in the field of nanotechnology, biomedicine, tissue engineering and drug delivery (Kutikov and Song, 2015; Li et al, 2017; Zhou et al, 2017; Park et al, 2018; Liua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…All of these characteristics of supramolecular biomaterials can potentially be achieved through rational design.Self-assembly is a key approach to form supramolecules through noncovalent interactions 6 . An amphiphilic molecule containing both hydrophobic and hydrophilic segments, when coming close to water, self-assembles into different shapes and sizes of supramolecules depending upon its nature [7][8][9] . Critical micelle concentration (CMC) is the minimum concentration at which stable micelle formation occurs.…”
mentioning
confidence: 99%